URBAN-RURAL GAP - INDIA'S BIGGEST HURDLE FROM A SOCIO-ECONOMIC PERSPECTIVE TO THE DEVELOPMENT OF THE NATION - Dr. Sumanta Bhattacharya,; Bhavneet Kaur Sachdev, (International Engineering Journal For Research & Development, 2021)
The rural society of India has remained backward over the years , it has not accepted much changes or allowed to changes to happen by a third part , lack of rural development has resulted in the migrant of people from rural to urban region for better lifestyle and living standards , the range of shifting is 75 million which is making the urban area over populated as it doesn’t have space for so many people , rural development is the key to stop this migrant and bridge the gap between the two regions . The government over the years have introduced and launched many schemes for the development of the rural areas but there have been many hurdles which didn’t allow development to take place from corruption to regional , traditional ways of thinking , social stigma , lack of education , climate change , skills and development followed by a number of reason , we need to bring in internet connectivity , electricity facilities in all the villages , compulsory schooling and introduction of colleges , construction of mandatory toilets in every household and bringing in artificial intelligence and machine learning and engineering for the development of the rural region .